RATTAN CRAFTSMANSHIP CENTER AND WOODWORKING KABUPATEN CIREBON - Karto Wijaya; Isti Qurani (Jurnal Arsitektur ARCADE, 2023)
Abstract: Local cultural assets include the cultural wealth of an area, both in physical and non-physical aspects that grow and develop from generation to generation. Craftsmanship tends to have a fairly broad exploration of ideas in making works or products of their creation. Rattan as a local product that has become part of the body of the people of Cirebon Regency, especially the Galmantro Rattan Tourism Village. The activities and potentials in this village seem to give a "soul" to Tegalwangi Village which is rarely owned by other villages. The potential of this activity finally gives identity to the area and buildings that are designed to use the â€œspirit of placeâ€as the Â concept theme from this planning programming. This theme connected through the genius loci of local wisdom which has several basic materials to be connected to the design concept, namely Nusantara Architecture. Architecture Nusantara includes: The existence of a terrace / porch as a communal space. Rattan Craftsmanship Center and Woodworking West Java, especially Cirebon Regency, is planned by considering the local materials and values of Nusantara Architecture.Keyword: Craftsmanship, Rattan, Nusantara ArchitectureAbstrak: Aset budaya local termasuk kedalamnya ialah kekayaan budaya sebuah daerah, baik dalam aspek fisik maupun non-fisik yang tumbuh serta berkembang secara turun-temurun. Craftsmanship cenderung memiliki eksplorasi ide yang cukup luas dalam membuat karya atau produk ciptaanya. Rotan sebagai produk lokal yang telah menjadi bagian tubuh dari masyarakat Kabupaten Cirebon khususnya Kampung Wisata Rotan Galmantro. Aktivitas dan potensi di kampung ini seakan memberikan â€œjiwaâ€ pada Desa Tegalwangi yang jarang dimiliki desa lain. Potensi dari kegiatan ini akhirnya memberikan identitas pada wilayah dan bangunan yang dirancang untuk menggunakan tema â€œspirit of placeâ€- nya dari kawasan ini. Tema ini kemudian terhubung melalui genius loci dari kearifan lokal budaya setempat yang memiliki beberapa material dasar untuk dapat dihubungkan kepada konsep perancangan, yakni Arsitektur Nusantara Arsitektur Nusantara diantaranya ialah : Adanya teras / serambi sebagai ruang yang dipakai secara komunal. Rattan Craftsmanship Center and Woodworking Jawa Barat, khususnya Kabupaten Cirebon, direncanakan dengan mempertimbangkan material dan nilai-nilai lokal Arsitektur Nusantara.Kata Kunci: Craftsmanship, Rotan, Arsitektur Nusantara